2002
DOI: 10.1089/152460902760360586
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cervical Screen Follow-Up among Low-Income Latinas: Project SAFe

Abstract: The intervention team--a peer counselor and a master's degreed social worker--addressed multiple psychosocial and systems navigation problems to reduce potential barriers to adherence, including knowledge, attitudinal, psychosocial, psychological distress, systems communication, and resource access problems. SAFe appears highly acceptable to women and may significantly enhance medical care management following an abnormal cervical screen for a carefully targeted group of women at risk for suboptimal follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 38 publications
2
96
1
1
Order By: Relevance
“…Prior studies have demonstrated the benefits of navigator programs for cancer prevention in general and for CRC screening in particular. [35][36][37][38][39][40][47][48][49] Tu et al's health educator study among US ethnic Chinese patients focused on FOBT rather than colonoscopy screening and showed a 5.98 increased odds for FOBT screening among intervention patients over the 6-month study. 41 A study using centralized telephone case management among low-income women increased rates of CRC screening by 13% (95% CI 7-20%) in intervention compared to usual care patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated the benefits of navigator programs for cancer prevention in general and for CRC screening in particular. [35][36][37][38][39][40][47][48][49] Tu et al's health educator study among US ethnic Chinese patients focused on FOBT rather than colonoscopy screening and showed a 5.98 increased odds for FOBT screening among intervention patients over the 6-month study. 41 A study using centralized telephone case management among low-income women increased rates of CRC screening by 13% (95% CI 7-20%) in intervention compared to usual care patients.…”
Section: Discussionmentioning
confidence: 99%
“…Work and child-care responsibilities also contribute to missed appointments 32,33 . Inadequate communication, our second most prominent systems barrier, was recognized and targeted in Project SAFe, which was designed to improve abnormal cervical screen follow-up among low-income Latinas 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The particular services provided by navigators depend on the barriers they identify and the strategies they adopt to eliminate or reduce those barriers. 18,19,29,30 This barrier-focused approach emerged clearly in the qualitative data. In the clinic we studied, navigators provided a variety of services, such as locating misplaced charts, interpreting for non-Englishspeaking patients, and providing emotional or educational support for patients and families.…”
Section: Defining Patient Navigationmentioning
confidence: 93%
“…Navigator programs have been established throughout the United States with support from private foundations, 19,31,32 in conjunction with grants from federal, state, and local government, 29,30,33 and through local initiatives by cancer centers, community-based clinics, and philanthropy. 19,34,35 Freeman et al's program in Harlem targeting "high incidence of late-stage cancer and poor prognostic outcomes of low-income and medically underserved minorities" has served as a paradigm for other navigation programs.…”
Section: How Navigator Programs Are Organizedmentioning
confidence: 99%